A collection of treaties, engagements and sanads relating to India and neighbouring countries Compiled by C.U. Aitchison, B.C.S., under secretary to the government of India in the Foreign department ... - India. Foreign and Political Department. (Tufts University. Tisch Library., 2017)
1 online resource (14 volumes) tables; Volume 14 of 14.; Tisch Outsourced Digitization 2017-10-02